Analisis Implementasi Sistem Informasi Akuntansi Penjualan Kredit Pada Koperasi Guru dan Pegawai di MAN 1 Sleman - Reza Alamsyah Harahap; Fajar Satriya Segarawasesa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Cooperatives as non-profit organizations must have an effective and adequate accounting information system. With a good accounting information system, it becomes an important basis for all operations that occur in a business organization. One of the objectives of the accounting information system is to improve the internal control structure of the company. The purpose of this study was to analyze the implementation of the credit sales accounting information system, in which credit sales also became a source of fixed income at the Amanah Cooperative MAN 1 Sleman, in order to determine the effectiveness of the credit sales accounting information system. This study applied descriptive analysis research with a qualitative approach, because it needed direct observation related to the object and subject under study. The data from this study were obtained through observation, interviews, and documentation at Amanah Cooperative MAN 1 Sleman. The results showed that the credit sales accounting information system at the Amanah Cooperative MAN 1 Sleman was still not effective and adequate, the function of the credit sales system was still inadequate with the presence of multiple tasks and the job description did not match the work in the field so that the tasks carried out become ineffective.